Age-dependent development of liver fibrosis in Glmpgt/gt mice. Issue 1 (December 2016) - Nesset, Cecilie; Kong, Xiang; Damme, Markus; Schjalm, Camilla; Roos, Norbert; Løberg, Else; Eskild, Winnie
Abstract Background Mice lacking glycosylated lysosomal membrane protein (Glmp gt/gt mice) have liver fibrosis as the predominant phenotype due to chronic liver injury. TheGlmp gt/gt mice grow and reproduce at the same rate as their wild-type siblings. Life expectancy is around 18 months. Methods Wild-type andGlmp gt/gt mice were studied between 1 week and 18 months of age. Livers were analyzed using histological, immunohistochemical, biochemical, and qPCR analyses. Results It was shown thatGlmp gt/gt mice were not born with liver injury; however, it appeared shortly after birth as indicated by excess collagen expression, deposition of fibrous collagen in the periportal areas, and increased levels of hydroxyproline inGlmp gt/gt liver. Liver functional tests indicated a chronic, mild liver injury. Markers of inflammation, fibrosis, apoptosis, and modulation of extracellular matrix increased from an early age, peaking around 4 months of age and followed by attenuation of these signals. To compensate for loss of hepatocytes, the oval cell compartment was activated, with the highest activity of the oval cells detected at 3 months of age, suggesting insufficient hepatocyte proliferation inGlmp gt/gt mice around this age. Although constant proliferation of hepatocytes and oval cells maintained adequate hepatic function inGlmp gt/gt mice, it also resulted in a higher frequency of liver tumors in older animals. Conclusions TheGlmp gt/gt mouse is proposed as a model for slowly progressing liver fibrosis and possibly as a model for a yet undescribed human lysosomal disorder.